Harmonisasi Undang-Undang Kepailitan Anak Perusahaan Badan Usaha Milik Negara (SETARA : Jurnal Ilmu Hukum, 2022)
This study aims to examine and analyze the harmonization of bankruptcy law concerning subsidiaries of State-Owned Enterprises (SOEs). Law Number 37 of 2004 does not provide an explanation regarding SOE subsidiaries, making harmonization of laws and regulations on the bankruptcy of SOE subsidiaries necessary. The method used in this research is normative legal research. The data used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Data analysis was conducted using a qualitative juridical method. The results show that harmonization between the Bankruptcy and Suspension of Debt Payment Obligations Law Number 37 of 2004 and the SOE Law Number 19 of 2003 confirms that an SOE subsidiary may be declared bankrupt by a party other than the Minister of Finance, because Article 2 paragraph (5) of Law Number 37 of 2004 applies only to SOEs operating in the public interest and not divided into shares, a form that under the SOE regime exists only in Perum.
Keywords: Harmonization; Bankruptcy; Subsidiary; State-Owned Enterprise; Perum